2016
DOI: 10.2147/opth.s80411
|View full text |Cite
|
Sign up to set email alerts
|

Role of steroids in the treatment of bacterial keratitis

Abstract: Bacterial keratitis can lead to severe visual impairment from corneal ulceration, subsequent scarring, and possible perforation. The mainstay of treatment is topical antibiotics, whereas the use of adjunctive topical corticosteroid drops remains a matter of debate. Herein, we review the rationale for and against the use of topical corticosteroids and we assess their effectiveness and safety in the published randomized controlled trials that have evaluated their role as adjunctive therapy for bacterial corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…In fact, although the use of corticosteroid in infectious keratitis remains controversial, 16 some authors believe that a judicious use of corticosteroids (combined with the appropriate antimicrobial) could improve the outcome of keratitis as it reduces damage caused by the host's inflammatory response, decreases corneal scarring, and inhibits neovascularization. 17,18 From a safety viewpoint, the use of corticosteroids is known to potentially delay corneal wound healing and exacerbate signs of ocular infection. In vitro , inhibition of corneal wound healing in dogs is only reported for prednisolone concentrations that are much higher (≥620 μg/mL) 19 than the ones reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although the use of corticosteroid in infectious keratitis remains controversial, 16 some authors believe that a judicious use of corticosteroids (combined with the appropriate antimicrobial) could improve the outcome of keratitis as it reduces damage caused by the host's inflammatory response, decreases corneal scarring, and inhibits neovascularization. 17,18 From a safety viewpoint, the use of corticosteroids is known to potentially delay corneal wound healing and exacerbate signs of ocular infection. In vitro , inhibition of corneal wound healing in dogs is only reported for prednisolone concentrations that are much higher (≥620 μg/mL) 19 than the ones reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…46 Clinical management of ocular infections is often challenging and requires close attention to controlling both the pathogen and host inflammation to preserve the visual axis. 7,8 Accordingly, it is important to consider the potential of vaccine- induced inflammatory responses during the initial stages of vaccine development when targeting pathogens that commonly affect the eye.…”
Section: Introductionmentioning
confidence: 99%
“…The role of combination in therapy in the management of corneal ulceration has been less definitive. In the Steroids for Corneal Ulcers Trial (SCUT), the use of steroids in acute ulceration was examined (Palioura et al 2016). This study found an overall lack of benefit, but also a lack of harm in using steroids in conjunction with antibiotics for the treatment of bacterial corneal ulcers.…”
Section: Combined Use Of Anti-infectives and Anti-inflammatories In Smentioning
confidence: 99%